Understanding contemporary models for organizational sustainability: critical review - Khalili, Amjad; Ismail, Md Yusof; Karim, A.N. Mustafizul (inderscience publishers, 2015)
This paper aims to critically review thirteen contemporary models and initiatives for Sustainable Development (SD). Sustainability is the action oriented variant of Sustainable Development. However, in the literature, there are mixed results regarding identification of the main dimensions of sustainability. Few efforts were done to compare between these models and show the similarities and dissimilarities aspects. Thus, different scholars have identified different models for measuring SD. As revealed through the analysis it is found that organizations are focusing on diversified aspects rather than identical or uniform strategies when dealing with sustainability issues. The main contributions of this paper are twofold; (1) it depicted thirteen different models for SD and (2) it introduced the different dimensions for SD compared with those from different scholars.